UPAYA PENINGKATAN PENDAPATAN NASIONAL PAJAK TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Widia Wulandari; Ratu Aaf Afifah; Nur Afni Aprilia; Dedek Kustiawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
One of the pillars of national income comes from tax revenues which contribute arround 70% of all state revenues. Taxes play a very important role in a country, without taxes a country’s life cannot run properly. Txes finance infrastructure development, education, health, fuel subsidies (BBM), payment of civil servants and construction of public facilities. Taxes are at the forefront of the development and economic growth of a country. Economic growth is the development of economic activity that occurs from time to time and causes real national income to grow. This study uses the method of literature study. The data obtained comes from books, scientific articles, and other douments that discuss national income, taxes and Indonesia’s economic growth. Economic growth can show the quality or achievement of the development of an economy from one period to the next. Economic growth has a positive impact on tax revenues, especially through increasing people’s income and consumption levels. The higher the economic growth accompanied by equal distribution on income, the higher the people’s income.